Social Assistance and Forced Displacement: A New Solution to an Old Problem? - Collyer, Michael; te Lintelo, Dolf; Mutambasere, Thabani; Zaman, Tahir (Refuge, 2024)
Social protection is a well-accepted means to tackle poverty. This article focuses on social assistance, one aspect of social protection primarily involving non-contributory transfers, in cash or in-kind. Forcibly displaced people, particularly those displaced across international borders, have typically been excluded from state-provided social assistance. This has begun to change. In addition, informal sources of social assistance—community organizations, neighbours, faith groups, and family networks—are particularly significant for displaced people. A more transformative understanding of social protection should encompass this wider array of sources. Interpreted in this way, social assistance offers a new way of bridging humanitarian and development responses to displacement.